2018
DOI: 10.7189/jogh.08.020805
|View full text |Cite
|
Sign up to set email alerts
|

Care seeking behaviour and aspects of quality of care by caregivers for children under five with and without pneumonia in Ibadan, Nigeria

Abstract: BackgroundThis study aimed to investigate the differences in reported care seeking behaviour and treatment between children with pneumonia and children without pneumonia with cough and/or difficult breathing.MethodsThree hundred and two children aged 0-59 months with fast breathing pneumonia were matched with 302 children seeking care for cough and/or difficult breathing at four outpatient clinics in Ibadan, Nigeria. After follow up at home, Demographic and Health Survey (DHS) and Multiple Indicator Cluster Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…Literature confirms that practices are similar in other low-income countries. [44][45][46] The main strength of this study is the inclusion of all ARTIs within a primary care clinic. This gives insight into the pathogens causing the infections.…”
Section: Discussionmentioning
confidence: 99%
“…Literature confirms that practices are similar in other low-income countries. [44][45][46] The main strength of this study is the inclusion of all ARTIs within a primary care clinic. This gives insight into the pathogens causing the infections.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Continuous nursing can serve to meet the needs of patients, improve the overall level of nursing, improve patient satisfaction, promote more effective nursing work, and promote improvement of the doctor-patient relationship. Kirolos et al 19 found that continuous nursing can improve nursing satisfaction among children with pneumonia as well as avoid medical disputes. The continuous nursing process is ongoing once the child leaves the hospital, urging children and families to adhere to nursing guidance and to carry out rehabilitation training, which has a good effect on patients' growth and development and improvement in their immune function while reducing the occurrence of complications; this is similar to research conducted by Huang et al 20 There are some limitations in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Kirolos et al. 19 found that continuous nursing can improve nursing satisfaction among children with pneumonia as well as avoid medical disputes. The continuous nursing process is ongoing once the child leaves the hospital, urging children and families to adhere to nursing guidance and to carry out rehabilitation training, which has a good effect on patients’ growth and development and improvement in their immune function while reducing the occurrence of complications; this is similar to research conducted by Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The level of education, motivation, and good behavior of mothers in giving special attention to their children about health care (immunization) can make an impact to prevent the onset of an infectious disease. This is evident from a study conducted, where the population that was observed had good immunization coverage (the universal child immunization status of the village was >95%), which meant that this population could prevent an infectious diseases (Kirolos et al, 2018).…”
Section: Immunization Statusmentioning
confidence: 93%